Distraction, distress and diversity: Exploring the impact of sensory processing differences on learning and school life for pupils with autism spectrum disorders - Jones, Elizabeth K.; Hanley, Mary; Riby, Deborah M. (Research in autism spectrum disorders, 2020)
•Sensory differences are seen to negatively affect school life for autistic pupils.•Teachers and parents believe sensory issues disrupt learning and school participation.•Sensory differences can cause anxiety, distress and distraction for autistic pupils.•A sense of agency, staff knowledge and resources can reduce sensory impacts.•Parents and teachers emphasize more training on ASD sensory processing is essential. Many individuals with Autism Spectrum Disorders (ASD) experience sensory differences that impact daily functioning. This study aimed to capture parent and teacher perspectives on how sensory differences affect learning and life at school for pupils with ASD. Fifty-seven parents and seventy UK teachers completed a bespoke online questionnaire that focused on the type of sensory experiences encountered at school and how these experiences impacted learning and school life for autistic pupils. Despite considerable heterogeneity in the experiences perceived as enjoyable or distressing, parents and teachers reported that sensory experiences at school were frequently negative. Data indicate that it was largely negative sensory experiences that impacted learning, in turn causing distraction, anxiety and limited participation. Although five teachers highlighted positive sensory experiences, the examples offered focused on children’s ability to engage in classroom activities, once their sensory needs had been met (e.g. using weighted blankets). Factors including predictability of sensory input, school resources, and staff knowledge minimized sensory disruption. According to teachers and parents, sensory experiences significantly impact learning and school life for autistic pupils and these findings can inform teacher training and intervention development.